KONSEP ERGONOMI DALAM MANAJEMEN PERKANTORAN PENDIDIKAN ISLAM: MENJAGA KESEJAHTERAAN DAN PRODUKTIVITAS KARYAWAN - Yusuf, M. (Program Studi Manajemen Pendidikan Islam (MPI) STAI Nahdlatul Ulama (STAINU) Malang, 2023)
This article aims to explore the role of ergonomics in the management of Islamic educational offices, with a focus on maintaining employee well-being and productivity. The background includes the context of office settings in Islamic education, the importance of office management, and the challenges faced. In the theoretical review, this research discusses the basic concepts of ergonomics, ergonomic principles in office settings, and their relationship with employee well-being and organizational productivity. The research method used is library research, collecting and analyzing relevant secondary data. The results of the study indicate that the implementation of ergonomic principles in the management of Islamic educational offices can provide significant benefits. The application of ergonomic workspace arrangement, appropriate equipment and furniture selection, optimal lighting and temperature regulation, as well as the provision of health facilities can enhance employee well-being and productivity. In the context of Islamic education, efforts to improve and enhance ergonomics in office management are crucial in creating a healthy, comfortable, and productive work environment. This article contributes to understanding the importance of ergonomics in the management of Islamic educational offices and proposes recommendations for practitioners and stakeholders to enhance work quality and employee well-being.